PROFESSIONAL INMUTATION OF JOURNALISTS: SPECIFICATION IDENTIFICATION - Холод, О. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article analyzes inmutation media and professional inmutation journalists. The problem is ignorance signs inmutation as mass communication and signs inmutation professional journalists. The aim of the study we chose identification and description of the signs inmutation mass communication and signs inmutation professional journalists. Research methodology we selected empirical and theoretical methods we applied to observation, which allowed us to advance due to certain features inmutation fix criteria of mass communication and features inmutation professional journalists. For the detail we asked the fixing method description. Among the methods of theoretical research we used formalization as a means of constructing abstract models aimed at the disclosure inmutation mass communication. We also touched upon the hypothetical-deductive method, which has allowed us to hypothesize about inmutation formation processes in mass communication and the process of professional journalists and inmutation prove the hypothesis deductive method. In the conclusion we came to a finding that the analysis of the specific two groups inmutation mass communication (those involved in the production of mass communication and that is a set of technical and technological factors) has given us the right to say that: inmutation those involved in the production mass communication, based on the social corrosion of core entities axiological scale of the individual; a set of technical and technological factors are simply the result of social corrosion (inmutation) society.